Artificial modulated Lewis pairs for highly efficient alkaline hydrogen production. (July 2022) - Xiao, Zehao; Yang, Mei; Liu, Canhui; Wang, Bowen; Zhang, Shilin; Liu, Jingyan; Xu, Zonglin; Gao, Ruijie; Zou, Ji-Jun; Tang, Aidong; Yang, Huaming
Abstract: Nickel phosphides are competitive non-noble candidates for alkaline hydrogen evolution reaction (HER), however, their activities are insufficient due to the inert alkaline water dissociation, which hampers application in hydrogen production. Herein, we design a highly efficient electrocatalyst consisting of monocrystalline NiMoO4 nanorods modified by broccoli-like hierarchical Ni(PO3 )2 -Ni2 P coupling with MoOx self-supported catalyst. As HER proceeds, catalytic performance gets better due to the dissolution of MoOx to further expose more nickel sites as Lewis base sites and in-situ formation of hydroxyl-ligands on the surface of loading nanoparticle as Lewis acid sites, which effectively integrate artificial frustrated Lewis pairs (FLPs) to respectively promote adsorption of H* and activation of H2 O molecules. Moreover, the electron-transfer leads to the downshift of the d -band center of Ni, which helps optimizing desorption ability of H* . Therefore, such reconstructed catalyst exhibits extremely low overpotentials of 11 and 79 mV to afford 10 and 100 mA·cm −2 in 1.0 M KOH with sustainable durability for over 110 h, outperforming most of reported advanced alkaline HER catalysts. Additionally, this catalyst used as cathode for overall alkaline water splitting at 10 and 100 mA·cm −2 with only 1.48 and 1.57 V, showing its broad application prospect in practical large-scale hydrogen production. Graphical Abstract: ga1 Highlights: Broccoli-like hierarchical Ni2 P-Ni(PO3 )2 nanoparticles are synthesized on vertical monocrystalline NiMoO4 nanorods. Dissolution of molybdenum results in more exposed active sites to further facilitate HER under alkaline conditions. Ni2 P and hydroxyl-ligands serve as frustrated Lewis pairs (FLPs) to promote desorption of H* and activation of H2 O. Reconstructed Ni-P-O catalyst exhibits efficient HER and overall water splitting activities with excellent durability.